ANALISIS LAYANAN DIGITAL DAN KEPUASAN TERHADAP LOYALITAS NASABAH PERBANKAN SYARIAH DI KABUPATEN JEPARA - Bahtiar, Siti; Ansori, Miswan (Wahana Islamika Jurnal Studi Keislaman, 2024)
This study aims to analyze the impact of digital services and customer satisfaction on customer loyalty in Islamic banking in Jepara Regency. With the increasing use of digital technology in the banking industry, it is essential to understand how digital services can affect customer satisfaction and loyalty. This research employs a quantitative approach with a sample of 86 Islamic bank customers in Jepara Regency. Data were collected through questionnaires distributed to respondents and analyzed using multiple linear regression analysis. The results show that digital services have a significant impact on customer satisfaction. Furthermore, customer satisfaction has a significant effect on customer loyalty. Effective and efficient digital services can enhance customer satisfaction, which in turn will increase their loyalty to Islamic banking. This study provides practical implications for Islamic banking management in improving the quality of digital services to strengthen customer loyalty.